A novel model for the cumulative plastic strain of soft marine clay under long-term low cyclic loads. (1st February 2018) - Ren, Xing-Wei; Xu, Qi; Teng, Jidong; Zhao, Nan; Lv, Le
Abstract: Long-term cyclic loads with a stress level lower than the critical cyclic stress applied on soft soil can lead to soil deformation but not to failure. The Monismith model is known for its simplicity and capacity to describe the cumulative plastic strain of soil under cyclic loads. However, it is unsuccessfully applied in these cases because the plastic strain in this model would increase endlessly till to failure with increasing number of load cycles. To solve this problem, a novel empirical model with three parameters is proposed based on analogy analysis of the Hardin-Drnevich model and Monismith model. The proposed model is verified by experimental data from existing literature and is shown to have better capability and performance than the Monismith model in predicting the cumulative plastic strain of soft soil subjected to long-term low cyclic loads. The value of parameter b is recommended to be 0.5, and relationships of parameters a and c with the cyclic stress ratio are also proposed for soft clay. Applications of the proposed model are elaborated in detail, and in situ test results for settlement of soft subgrade are used to evaluate the performance of this model. The prediction results are consistent with the test results. The research results present a promising method for investigating the development of deformation and the settlement of soft foundation in the near-shore and off-shore areas caused by wave and/or traffic loads. Highlights: A novel prediction model for strain of marine clay under cyclic load is proposed. The model is verified and validated by numbers of dynamic triaxial test data. Relations between model parameters and stress state and soil state are presented. The new model has a better prediction performance than Monismith model.